Leveraging Space Science and Technology for Climate-Induced Disaster Management in Pakistan - Ibrar ul Hassan Akhtar; Maryam Mehboob (CISS Insight Journal, 2025)
The frequency and severity of climate-related disasters, such as floods, droughts, heatwaves, and glacier melt, are on the rise and pose serious threats to vulnerable countries. Due to warming temperatures, changing rainfall patterns, and glacier melting, Pakistan is facing increased risks to its agriculture, water resources, infrastructure, and human security. This paper discusses how space science and technology can play a pivotal role in improving Pakistan’s ability to deal with climate-led disasters. It also examines the institutional arrangements, technological tools, and national politics that facilitate the integration of Earth Observation (EO), satellite remote sensing, Geographic Information Systems (GIS), and Artificial Intelligence (AI) in Disaster Risk Reduction (DRR) and early warning systems. Efforts of Space and Upper Atmosphere Research Commission (SUPARCO), its collaborations with national and international agencies, satellite programs like Remote Sensing Satellite System (PRSS) and Pakistan Remote Sensing Satellite - Earth Observation 1 (PRSC-EO), as well as its contribution to research initiatives like the Space Application Center for Response in Emergency and Disaster (SACRED) and the Natural Catastrophe Modelling (NatCat) initiative are discussed in detail in this study. Drawing on international best practices from countries such as China, Japan, and the United States, this paper examines how emerging technologies like big data analytics, Machine Learning (ML), and high-performance computing are transforming disaster management. While Pakistan has made significant progress in this area, it still faces major challenges, including a lack of satellite infrastructure, inadequate funding, poor inter-agency coordination, and difficulties with last-mile data application. The paper concludes that with continued investment, improved institutional cooperation, and capacity-building efforts, Pakistan can effectively leverage space-based solutions to enhance climate resilience and reduce disaster risks.